2019
DOI: 10.3748/wjg.v25.i34.5017
|View full text |Cite
|
Sign up to set email alerts
|

Reducing anastomotic leak in colorectal surgery: The old dogmas and the new challenges

Abstract: Anastomotic leak (AL) constitutes a significant issue in colorectal surgery, and its incidence has remained stable over the last years. The use of intra-abdominal drain or the use of mechanical bowel preparation alone have been proven to be useless in preventing AL and should be abandoned. The role or oral antibiotics preparation regimens should be clarified and compared to other routes of administration, such as the intravenous route or enema. In parallel, preoperative antibiotherapy should aim at targeting c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
43
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 81 publications
(84 reference statements)
1
43
0
5
Order By: Relevance
“…20 Similar results were recently reported in the setting of open or even minimally invasive colon resections. 13,21,22 We have also found decreased rates of infectious complications, including wound infections and intraabdominal abscesses, and ileus among patients in MBP and OABx. These observations are in agreement with Kiran and coworkers who demonstrated that preoperative antibiotics in combination with mechanical bowel preparation resulted in almost 50% reduction in postoperative infectious complications and ileaus.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…20 Similar results were recently reported in the setting of open or even minimally invasive colon resections. 13,21,22 We have also found decreased rates of infectious complications, including wound infections and intraabdominal abscesses, and ileus among patients in MBP and OABx. These observations are in agreement with Kiran and coworkers who demonstrated that preoperative antibiotics in combination with mechanical bowel preparation resulted in almost 50% reduction in postoperative infectious complications and ileaus.…”
Section: Discussionmentioning
confidence: 54%
“…12 In this context, MBP is supposed to enhance the uptake of OABx by colonic mucosa. 13 This concept was supported by the documented advantage of oral over intravenous antibiotics when administered after MBP as preparatory measure before colon and rectal resections. 14 Thus, the mitigation of AL and SSI rates in patients who received MBP prior to elective left colectomy could be attributed to the synergistic effect induced by combining MBP and OABx.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated a rate of AL of 4%-29 %, [11][12][13][14] and several risk factors for AL after colorectal cancer surgery have been discussed [20][21][22], as well as methods to reduce the rate, prevent AL, and the related risk factors [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…У больных группы 2 встречались единичные осложнения (частичная несостоятельность анастомоза класса В -у 2 (14,3%) больных, серома послеоперационной раны -у 2 (14,3%) больных, тогда как частичной несостоятельности анастомоза класса С, перитонита или лимфореи не наблюдалось. Количество дней от операции до выписки у больных группы 2 было меньшим и составило 9 [7][8][9][10][11][12][13] дней по сравнению с 13,0 [9-20] днями у больных группы 1. У больных раком прямой кишки после передней резекции прямой кишки выбор хирургической тактики наложения аппаратных колоректальных анастомозом «конец-в-конец» и «конец-в-бок» влияет на частоту развития несостоятельности анастомозов; наложение анастомозов «конец-в-бок» уменьшает частоту и тяжесть несостоятельности колоректальных анастомозов, что способствует сокращению послеоперационного восстановительного периода.…”
unclassified